(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Marketing contracts are considered one of the key tools that can support the shift towards sustainable development. They represent a legal and regulatory commitment between the concerned parties, aiming to market products or services in a way that contributes to achieving sustainable development goals. The impact of marketing contracts extends beyond the mere promotion of products or services, encompassing broader effects on the environment, society, and the economy. This research aims to analyze the role of marketing contracts in promoting sustainable development within the General Company for Pharmaceutical and Medical Supplies in Samarra. Data collection for the theoretical aspect involved using Iraqi, Arab, and foreign books, as well as theses and dissertations. For the practical aspect, the study relied on available data and information regarding marketing contracts to warehouses and private scientific offices, franchise agreements with private factories, and reports from regulatory bodies affiliated with the Federal Board of Supreme Audit relevant to the study period. Despite the quality of the company’s products, the study concluded with several findings, including the prevalence of low-quality medicines in local markets due to weak pharmaceutical media and a lack of marketing outlets, along with a deficiency in effective marketing programs to enhance the company’s brand and increase its market share.